Synthesis and biological evaluation of shikimic acid derivatives - Nguyen, Van Hung; Pham, Van Cuong; Mai, Huong Doan Thi; Le, Thanh Nguyen; Nguyen, Thi Minh Hang; Vu, Van Nam; Tran, Huu Giap; Do, Thi Thao; Dehaen, Wim; Chau, Van Minh (European Journal of Chemistry, 2014)
From shikimic acid, new series of oseltamivir analogues containing either ether sulfur or ether oxygen at C-3 position were prepared and evaluated for their biological activities. This is the first report on synthesis of oseltamivir analogues with ether sulfur at C-3. Except for compounds 4d, 4f, 7c and 7d, the remaining compounds were found to be active against MCF-7, LU-1 and KB cell lines. As oseltamivir had no cytotoxicity against different cell lines such as MCF-7, LU-1, KB, MDCK, MRC-5, VERO, MK and 293, the modification of alkyl groups at C-3 of the oseltamivir ring framework could significantly increase the cytotoxicity for this class of compounds. Loss of neuraminidase inhibition activity of these synthetic oseltamivir analogues suggested that the alkyl ether groups at C-3 should be critical for their anti-neuraminidase activity.